Analisis Economic Value Added (EVA) Dan Return On Asset Sebagai Alat Mengukur Kinerja Keuangan Pada Salah Satu Bank BUMN Terdaftar Di Bursa Efek Indonesia Periode 2019 – 2023 - Listiana, Iwin (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2024)
The objective of this research is to investigates the financial performance of BUMN Bank listed on IDX during the period 2019-2023 using Economic Value Added (EVA) and Return on Assets (ROA). The data analysis techniques in this research is a qualitative methode. The result of this research is the average of Economic Value Added (EVA) was Rp. 3.904.565.083, indicating positive EVA values (> 0). The average amount Return On Assets (ROA) during the period 2019-2023 was 2.25%. Showing that BUMN Bank have achieved economic value addition and generated statisfactory profits. Therefore, stakeholders can trust their investments in the bank.